PENGETAHUAN IBU HAMIL TENTANG ANEMIA DALAM KEHAMILAN - dewi, ovi puspita; Ni Wayan, Sukma Adnyani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Anemia of pregnancy can cause high morbidity and mortality rates. This study aims to explore the maternal knowledge level of anemia of pregnancy reviewed based on age, education and parity. This study has 30 samples. The results shows that the maternal knowledge level of anemia on pregnancy is as follows: mothers <20 years of age had low level of knowledge (77,78%); mothers with low education had low level of knowledge (80%); and primigravid mothers had low level of knowedge as well (75%). Thus, it can be concluded that low level of knowledge regarding anemia on pregnancy can generally be found in mothers whose age is <20 years, with low education, and who are expecting their first child.